English vocabulary in use - Michael McCarthy (Cambridge University Press, 1999)
The first in the family of best-selling vocabulary reference and practice books from elementary to advanced level. Vocabulary is clearly presented and contextualized on left-hand pages with practice activities on facing right-hand pages. This book is primarily designed as a self-study reference and practice text but it can also be used for classroom work. It is beautifully illustrated in full colour and contains 60 units. Vocabulary is presented in context and there are plenty of follow-up exercises. This edition includes an answer key